“Am I one of them ones”: autoethnographic reflections of an African American administrator on educational reform in predominantly White communities - Cheeks, Brandon Jamaal (Kansas State University, 2024)
Here I offer a critical autoethnography as an African American Male who has engaged in various forms of educational reform in predominantly White communities. My personal stories will take you on a journey of my life and career in education as a teacher and leader through counter-storytelling with a focus on my experiences in administrative positions. Using critical race theory, along with diversity and reform frameworks found in the Kansas State Department of Education to guide my self-analysis, I offer stories which highlight my unique perspectives as a leader. While this story began with a specific focus on educational reform in Kansas, it ultimately evolved into a more personal story of growth and self-awareness which culminates with my reaction to a question posed by Gloria Ladson-Billings (2023) during a Keynote address: “Are you one of them ones?”
Keywords: Educational reform; Autoethnography; Diversity; Equity; Inclusion; Belonging